New current mode biquadratic active filters employing currentdifference amplifiers - Abuelma’atti, M.T. (1994)
A new configuration for realization of current mode active filters is presented. It can synthesize current-mode second-order allpass, bandpass, highpass, lowpass and band-eliminate filter sections using a single current difference (Norton) amplifier and at most seven passive RC one-port elements